ETHANOL PRODUCTION FROM OIL PALM EMPTY FRUIT BUNCH AND ITS ACID HYDROLYSIS USING MICROBIAL CELLULASE SACCHARIFICATION - Hamka Nurkaya (PROSIDING SEMINAR KIMIA, 2014)
Oil palm empty fruit bunch (OPEFB) is a co mmon solid waste fro m the palm oil industry that requires proper handling to be processed into bioethanol as new bioenergy source to substitute fossil fuel, oil, gas, and coal. Microbial applications have been considered an effective way to degrade a lignocellulosic bio mass into simple sugars as a critical material for b ioethanol production . A potential of using OPEFB and The residue of the acid hydrolysis of the OPEFB to accelerate cellulase activity and reducing sugar production of Steptomyces hirsutus isolate 12.3.A was tested. The optimal conditions for cellu lase production by S. hirsutus isolate 12.3.A were similar for both substrates. The best yields were derived fro m culturing the cells at pH 7, 30°C, and substrate concentration at 1% for 6 days and amonium sulfate is the best as a nitrogen source for OPEFB med iu m and peptone is the best as nitrogen sources for the residue medium. The highest cellulase activit ies fro m OPEFB and the acid hidrolysis residue were 0.71 U/ ml and 0.56 U/ ml, respectively. Specific activity fro m ammoniu m sulfate precipitation was raised as 3.74 U/ mg and for cellu lase purificat ion by dialysis was 7.38 U/ mg. The in itial concentration of reducing sugar for OPEFB and the residue med iu m were 1.77 g/l and 1.01 g/l while the optimal ethanol production from OPEFB and the residue as sugar sources were 0.76 g/l and 0.41 g/l at inc ubation times of 72 hours.